The Effectiveness of Feminist Group Counselling with Expressive Writing Techniques to Improve Self-compassion for Student Victims of Sexual Harassment - Apriani, Rizka; Fauziah Ilmi Qonita; Yuliati Hotifah (Bisma The Journal of Counseling, 2025)
Sexual harassment can have long-term negative effects on victims, one of which is a decrease in self-compassion. A decline in self-compassion may hinder the achievement of individuals’ developmental tasks. This study aims to analyze the effectiveness of feminist counseling services using expressive writing techniques to enhance self-compassion among students who are victims of sexual harassment. The research employed a quantitative approach with a one-group pretest-posttest experimental design. The study population consisted of 60 students who had experienced sexual harassment. The data collection instrument used was a self-compassion scale developed by Kristin Neff and translated by Sugianto et al. The sample consisted of six female students with low levels of self-compassion who were selected using purposive sampling techniques. These six students received feminist group counseling interventions using expressive writing techniques over five sessions. Data were analyzed using the non-parametric Wilcoxon Signed Ranks Test. The analysis yielded a Z value of -2.207 and an asymp. sig. (2-tailed) value of 0.027, which is lower than the alpha level of 0.05, indicating a significant increase in scores before and after the intervention. Therefore, it can be concluded that feminist group counseling with expressive writing techniques is effective in enhancing self-compassion among students who are victims of sexual harassment.